Arterial chemoembolisation with cisplatin versus epirubicin for hepatocellular carcinoma (ACE 500 study): A multicentre, randomised controlled phase 2/3 trial. (November 2021) - Aramaki, Osamu; Takayama, Tadatoshi; Moriguchi, Masamichi; Sakamoto, Hidemori; Yodono, Hiraku; Kokudo, Norihiro; Yamanaka, Naoki; Kawasaki, Seiji; Sasaki, Yo; Kubota, Keiichi; Otsuji, Eigo; Tanaka, Shinji; et al.
Abstract: Background: Transarterial chemoembolisation (TACE) is a treatment option for hepatocellular carcinoma (HCC), but the optimum agent for TACE remains unclear. We compared the efficacy of TACE with cisplatin versus with epirubicin in patients with unresectable HCC. Methods: This multicentre, randomised, phase 2/3 trial was performed at 21 hospitals in Japan. Patients with liver-confined HCC, performance status 0–2, and Child-Pugh class A/B were randomised to receive TACE with cisplatin or epirubicin. Patients were stratified in accordance with the institution, Child-Pugh class, tumour size, tumour thrombosis, α-fetoprotein and prior treatment. The primary end-point was overall survival in the intention-to-treat population. Tumour response was evaluated in accordance with the Response evaluation criteria in solid tumours criteria. Findings: Between 2008 and 2012, 455 patients were randomly assigned to undergo TACE with cisplatin (n = 228) or epirubicin (n = 227). Eleven patients were ineligible, and 444 patients were included in the full analysis. Twelve patients not receiving TACE were excluded, and 432 patients were included in the safety analysis set. In phase 2, disease control rates in cisplatin (91·7%) and epirubicin (91·8%) groups exceeded the predefined threshold of 70%, and the study proceeded to phase 3. After a median follow-up of 32·7 months (IQR = 15·3–49·3), median overall survival periods were 2·93 years (95% CI 2·60–3·79) and 2·74 years (95%CI 2·26–3·21), respectively (hazard ratio 0·90 [95% CI 0·71–1·15], p = 0·22). Median times to treatment failure were 1·38 and 1·46 years (hazard ratio 1·09 [95% CI 0·88–1·35], p = 0·88), response rates were 65·3% and 60·6% (p = 0·31), and serious adverse event rates were 49·8% and 48·3% (p = 0·56), respectively. No treatment-related deaths occurred in either group. Interpretation: In our phase 2/3 randomised trial, cisplatin is not significantly superior to epirubicin in TACE for patients with HCC. Highlights: Transarterial chemoembolisation (TACE) is a treatment option for hepatocellular carcinoma. There is no clear consensus regarding the optimal chemotherapeutic agent for use in TACE. Few studies have compared agents used for TACE. Cisplatin is not significantly superior to epirubicin in TACE for patients with HCC.